A Rationality Immersed in Religiosity: Reason and Religiosity in Abu'l Fazl's Oeuvre. (May 2020) - Mukhia, Harbans
Abu'l Fazl is often invested with a dichotomy between reason and religion, grandly upholding the majesty of reason ( mā'qūlāt ) over received blind faith ( taqlīd ), drawing inspiration from varied sources but falling short of going the distance towards 'scientific rationality'. Abu'l Fazl's rationality had little in common with it; it was rooted in a new dichotomy he was constituting, one between universal religiosity and denominational religions, thus redefining dīn. Sulh-i kul (Absolute peace) in the midst of religious strife was his rationality. It is suggested that the main inspiration for this dichotomy came from the saint-poet Kabir, even as Abu'l Fazl was greatly influenced by the Sufi doctrines of 'Illumination' of the Eastern School and wahdat al-wujūd of Ibn al-'Arabi.